Prevalent diabetes and risk of total, colorectal, prostate and breast cancers in an ageing population: meta-analysis of individual participant data from cohorts of the CHANCES consortium - Amadou, A; Freisling, H; Jenab, M; Tsilidis, KK; Trichopoulou, A; Boffetta, P; Van Guelpen, B; Mokoroa, O; Wilsgaard, T; Kee, F; Schöttker, B; Ordóñez-Mena, JM; et al. (Springer Nature, 2021)
Background We investigated whether associations between prevalent diabetes and cancer risk are pertinent to older adults and whether associations differ across subgroups of age, body weight status or levels of physical activity.